EXPLORING CULTURAL ACCULTURATION: RITUALS AND SPIRITUAL PRACTICES OF TRADITIONAL CHILDBIRTH IN NANJUNG, BANDUNG REGENCY, WEST JAVA, INDONESIA - Kokom Siti Komariah; Mohammad Rindu Fajar Islamy; Nurti Budiyanti; Muhamad Parhan (Religio Education, 2021)
Indonesia is a multicultural country that has so much diversity, among which is the diversity of religions and customs or cultures. Cultural acculturation has a significant impact on the construction of thought and ritual practices carried out by a society. The purpose of this study was to analyze and analyze the practice of traditional child birth carried out by the community in Nanjung Village, Bandung Regency, West Java, Indonesia. The research method used in this study is an ethnographic approach. The author tries to make a visit to the site, then interviewed single information interactively to find the data needed in this study. The data obtained were then analyzed using the theory of acculturation and Islamic religious perspective. The findings prove that the practice of customary childbirth carried out by the perpetrator is a cultural acculturation process. The practice of child birth is at least one way in the context of maximum efforts so that the baby can survive and develop into a pious child